2016
DOI: 10.1177/0148607116680791
|View full text |Cite
|
Sign up to set email alerts
|

Independence From Parenteral Nutrition and Intravenous Fluid Support During Treatment With Teduglutide Among Patients With Intestinal Failure Associated With Short Bowel Syndrome

Abstract: Background: In phase III clinical studies, treatment with teduglutide was associated with clinically meaningful reductions (≥20% from baseline) in parenteral support (PS; parenteral nutrition and/or intravenous fluids) requirements in adult patients with intestinal failure associated with short bowel syndrome (SBS-IF). This analysis reports clinical characteristics of patients who achieved complete independence from PS during teduglutide treatment. Materials and Methods: Post hoc analysis of adult patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 14 publications
3
52
1
3
Order By: Relevance
“…Total amount of intravenous fluid and calorie uptake per week was significantly reduced over time, but it took longer than previously reported in a randomized and controlled clinical trial. 26 Interestingly, as reported previously, 32 baseline characteristics for amount of parenteral support before the start of treatment did not strictly determine the effect of teduglutide. Patients initially on daily parenteral support showed a strong improvement after treatment over 1 year.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Total amount of intravenous fluid and calorie uptake per week was significantly reduced over time, but it took longer than previously reported in a randomized and controlled clinical trial. 26 Interestingly, as reported previously, 32 baseline characteristics for amount of parenteral support before the start of treatment did not strictly determine the effect of teduglutide. Patients initially on daily parenteral support showed a strong improvement after treatment over 1 year.…”
Section: Discussionmentioning
confidence: 84%
“…This finding is consistent with recently published real-life data 29 as well as the post hoc analysis of the phase III placebo-controlled trials. 30 This observation is supported by the high physiological expression of the GLP-2 receptor in the colon.…”
Section: Discussionmentioning
confidence: 88%
“…A review looking at studies that included a total of 134 patients on HPN treated with teduglutide showed that 12% of HPN patients were able to completely discontinue their PN and others were able to decrease the number of days they needed PN 64 . While it potentially improves quality of life for these patients, if the patients no longer meet the Medicare guidelines for the number of calories needed to come from HPN or are able to decrease the number of days of infusion, as has been shown, it may put coverage for HPN in jeopardy 70 , 71 …”
Section: Other Challengesmentioning
confidence: 99%
“…64 While it potentially improves quality of life for these patients, if the patients no longer meet the Medicare guidelines for the number of calories needed to come from HPN or are able to decrease the number of days of infusion, as has been shown, it may put coverage for HPN in jeopardy. 70,71…”
Section: Other Challengesmentioning
confidence: 99%
“…SBS shares a common trait with AN: both are bone catabolic disorders. On the other hand, while AN is a condition of self‐imposed caloric restriction, in SBS, individuals receive calorie replacement through parenteral and enteral nutrition . No previous study that we are aware of has assessed the relationship between MAT and bone mass in individuals taking artificial nutrition.…”
Section: Introductionmentioning
confidence: 99%